Sistem Peringatan Dini Kebakaran Dan Kebocoran Gas LPG Berbasis Notifikasi SMS Gateway - Dedi Satria (Jurnal Informatika, 2023)
This article discusses the development of an Early Warning System for Fires and LPG Gas Leaks Based on SMS Gateway Notifications which aims to improve safety in the household environment. This system consists of several main components, including a fire sensor, MQ-2 smoke sensor, MQ-6 LPG gas sensor, DHT11 temperature sensor, Arduino Uno as a data processor, and a Wavecom GSM modem as an SMS-based notification sender. This system succeeded in detecting fires at an early stage through fire sensors and smoke sensors, as well as LPG gas leaks through LPG gas sensors. When danger detection occurs, the system provides users with instant SMS-based notifications, giving them valuable time to take necessary precautions or evacuation. The system shows a high level of accuracy in detecting danger, avoiding false alarms that annoy users. User response to this system has been very positive, and SMS notifications are considered very useful in providing early warning. Household safety becomes better thanks to the use of this technology. Additionally, this system has the potential for further development and integration with existing household security systems. In conclusion, this Early Warning System has great potential to improve household safety and security in the future.